2018
DOI: 10.1515/chem-2018-0129
|View full text |Cite
|
Sign up to set email alerts
|

Content of Zn, Cd and Pb in purple moor-grass in soils heavily contaminated with heavy metals around a zinc and lead ore tailing landfill

Abstract: The paper presents concentrations and correlations between Zn, Cd and Pb in the aboveground parts of purple moor-grass (Molinia caerulea L.) in forest soils heavily contaminated with heavy metals around a zinc and lead ore tailing landfill at Mining & Metallurgy Enterprise “Bolesław” SA in Bukowno. Field observations have indicated that purple moor-grass, which occurs as one of the few vascular plants in locations with tailing mud, is probably a species with high adaptability to conditions in contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Researchers, including Neila et al ( 2017 ), Damek-Poprawa and Sawicka-Kapusta ( 2004 ), Durkalec et al ( 2015 ), Antonkiewicz et al ( 2018 ), also demonstrated the importance of inter-species and individual differences resulting from adaptive processes related to inheritance of resistance in a given population or a given individual with increased resistance to high metal concentrations in the environment. Such resistance, involving the ability to exclude excess xenobiotics from metabolism or deposit them in specific organs, increases tolerance and changes the toxicity threshold (Kicińska 2016 ; Kicińska and Jelonek-Waliszewska 2017 ; Kołacz et al 2003 ; Pietrzykowski et al 2018 ). One such organ, especially with regard to metal accumulation, is the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers, including Neila et al ( 2017 ), Damek-Poprawa and Sawicka-Kapusta ( 2004 ), Durkalec et al ( 2015 ), Antonkiewicz et al ( 2018 ), also demonstrated the importance of inter-species and individual differences resulting from adaptive processes related to inheritance of resistance in a given population or a given individual with increased resistance to high metal concentrations in the environment. Such resistance, involving the ability to exclude excess xenobiotics from metabolism or deposit them in specific organs, increases tolerance and changes the toxicity threshold (Kicińska 2016 ; Kicińska and Jelonek-Waliszewska 2017 ; Kołacz et al 2003 ; Pietrzykowski et al 2018 ). One such organ, especially with regard to metal accumulation, is the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium accumulation patterns in plants vary in tolerant, nontolerant and hyperaccumulating species [4,9]. Metal hyperaccumulating plants have high concentrations of Cd in the dry mass but produce little biomass, which results in low metal absorption per area [15,20].…”
Section: Cadmium Concentration In Shoot and Phytolithmentioning
confidence: 99%
“…Plants in better nutritional status are more tolerant to adverse growth factors [8,22], and Megathyrsus maximus has a higher production potential compared to Urochloa sp., being more responsive to soil fertilization [21]. However, production and elemental composition of phytoliths are influenced by element availability and absorption, climatic conditions (transpiration flow), plant species, silicon concentration and soil type, variety, location, disease resistance and fertilizer requirements [5,6,20,28,29].…”
Section: Cadmium Concentration In Shoot and Phytolithmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important contaminants are heavy metals in sediments of tailing ponds and heaps. The burden manifests itself across all components of the earth's land sphere [5][6][7][8][9][10] or within individual components: air [11], water [12][13][14][15], soil [11,12,[16][17][18][19][20][21][22][23][24][25], and flora and fauna [15,[26][27][28]. Last but not least, the negative effect of these or similar forms is also manifested in humans [10,19,29,30].…”
Section: Introductionmentioning
confidence: 99%